Boundary effects on the Soil Water Characteristic Curves obtained from lattice Boltzmann simulations. (January 2016) - Galindo-Torres, S.A.; Scheuermann, A.; Li, L.
Abstract: Pore-scale simulations using a Lattice Boltzmann Method (LBM)-based numerical model were conducted to examine how the capillary pressure ( P c ) and saturation ( S ) evolve within a virtual porous medium subjected to drainage and imbibition cycles. The results show the presence of a sharp front (interface separating the wetting and non-wetting fluids) across the cell during the test, which expectably moves up and down as the controlling non-wetting fluid pressure at the upper boundary varies to simulate different P c levels over the drainage and imbibition cycle. This phenomenon, representing inhomogeneity at the simulated scale, is in conflict with the homogenization applied to the pressure cell for deriving the constitutive P c – S relationship. Different boundary conditions, adopted to achieve more homogeneous states in the virtual soil, resulted in different P c – S curves. No unique relationship between P c and S, even with the interfacial area ( A nw ) included, could be found. This study shows dependence of the LBM-predicted P c – S relation on the chosen boundary conditions. This effect should be taken into account in future numerical studies of multiphase flow within porous media.